2014
DOI: 10.1186/1749-8104-9-17
|View full text |Cite
|
Sign up to set email alerts
|

Pioneer midbrain longitudinal axons navigate using a balance of Netrin attraction and Slit repulsion

Abstract: BackgroundLongitudinal axons grow parallel to the embryonic midline to connect distant regions of the central nervous system. Previous studies suggested that repulsive midline signals guide pioneer longitudinal axons by blocking their entry into the floor plate; however, the role of midline attractants, and whether attractant signals may cooperate with repulsive signals, remains unclear. In this study we investigated the navigation of a set of pioneer longitudinal axons, the medial longitudinal fasciculus, in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 67 publications
(92 reference statements)
1
29
0
Order By: Relevance
“…As combined Netrin-1 and Robo mutations caused a lethal genetic interaction, we obtained only one Netrin-1/Robo1/2 triple homozygous mutant embryos even though they are predicted at 1/16 ratios, which we previously reported (Kim et al, 2014). The triple mutant had the Netrin-1 − and β-galactosidase + floor plate (Fig.…”
Section: Methodsmentioning
confidence: 54%
See 2 more Smart Citations
“…As combined Netrin-1 and Robo mutations caused a lethal genetic interaction, we obtained only one Netrin-1/Robo1/2 triple homozygous mutant embryos even though they are predicted at 1/16 ratios, which we previously reported (Kim et al, 2014). The triple mutant had the Netrin-1 − and β-galactosidase + floor plate (Fig.…”
Section: Methodsmentioning
confidence: 54%
“…To assay axon outgrowth, explants were cultured with or without Netrin-1 (200 ng/ml) for 48 hours. To assay directional effects, localized Netrin-1 sources were provided as described in our previous paper (Kim et al, 2014). Explants are co-cultured with aggregates of COS-7 cells transfected with no plasmid (mock) or Netrin-1 expression plasmid (gift of Marc Tessier-Lavigne, Rockefeller) for 48 hours.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…An example that may be more similar to the mechanism that we have uncovered for motor neurons is the parallel independent Netrin and Slit guidance of fly commissural axons (Garbe and Bashaw, 2007). In another recent study, we have shown that simultaneous Netrin-1/DCC and Slit/Robo signals guide pioneer longitudinal axons through the mouse hindbrain, providing further evidence of neurons that balance Netrin1 attraction and Slit repulsion (Kim et al, 2014). …”
Section: Discussionmentioning
confidence: 65%
“…Finally, we show a genetic interaction between NFM-1 and the secreted guidance cue SLT-1 in AQR migration. In vertebrates, Slit1 and Slit2 are required for guidance of many axons, acting through the Robo family receptors (Nguyen Ba-Charvet et al 1999;Piper et al 2000;Bagri et al 2002;Unni et al 2012;Kim et al 2014). The Slit-Robo guidance pathway is conserved in C. elegans, where SLT-1 acts as a guidance cue for several neurons through SAX-3/Robo (Hao et al 2001;Chang et al 2006;Quinn et al 2006;Xu and Quinn 2012).…”
mentioning
confidence: 99%